2016
DOI: 10.1590/0102-6720201600s10010
|View full text |Cite|
|
Sign up to set email alerts
|

Gastric and Jejunal Histopathological Changes in Patients Undergoing Bariatric Surgery

Abstract: Background:Morbid obesity is a multifactorial disease that increasingly is being treated by surgery. Aim: To evaluate gastric histopathological changes in obese, and to compare with patients who underwent gastrojejunal bypass and the jejunal mucosa after the surgery. Methods:This is an observational study performed at a tertiary public hospital, evaluating endoscopic biopsies from 36 preoperative patients and 35 postoperative. Results:In the preoperative group, 80.6% had chronic gastritis, which was active in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…One study in humans showed that chronic low-grade inflammation of the gastric area and the jejuna significantly reduces at least 1 year after RYGB in patients with or without T2D, in concert with reduction of T2D rate from 41.7 % in preoperation to 11.4 % in postoperation cases [80]. Another intestinal biopsy study shows that RYGB down-regulates the expression of jejunal toll-like receptor 4 (TLR4), which mediates pro-inflammatory mediators in patients with complete and partial T2D remission 3 months after surgery, and the expression of TLR7 in the jejunum is significantly different between complete remission and partial T2D remission [81].…”
Section: Intestinal Low-grade Inflammationmentioning
confidence: 99%
“…One study in humans showed that chronic low-grade inflammation of the gastric area and the jejuna significantly reduces at least 1 year after RYGB in patients with or without T2D, in concert with reduction of T2D rate from 41.7 % in preoperation to 11.4 % in postoperation cases [80]. Another intestinal biopsy study shows that RYGB down-regulates the expression of jejunal toll-like receptor 4 (TLR4), which mediates pro-inflammatory mediators in patients with complete and partial T2D remission 3 months after surgery, and the expression of TLR7 in the jejunum is significantly different between complete remission and partial T2D remission [81].…”
Section: Intestinal Low-grade Inflammationmentioning
confidence: 99%